NILAI AKTIVA BERSIH REKSA DANA SYARIAH: DITINJAU DARI ASPEK INFLASI, KURS, BI 7 DAYS REPO RATE DAN TINGKAT RETURN - Evan Hamzah Muchtar; Irwan Maulana; Shelly Silviani (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
Islamic mutual funds are an alternative for Muslim people who want to invest with a small capital and minimal time and knowledge. One of the benchmarks for the performance of Islamic mutual funds is Net Asset Value. This article aims to examine the effects of inflation, exchange rates, the BI 7 Days Repo Rate and the rate of return on Net Asset Value. The sample in this study is time series data obtained from PT Danareksa Investment Management, the Financial Services Authority and Bank Indonesia for the period January 2015 to December 2019. The analysis technique used in this study is the Vector Error Correction Model to determine the long-term and short-term effects with using eviews software 8. Based on the long-term test results, the rate of return has a positive effect on Net Asset Value. Inflation has a positive effect on Net Asset Value. Exchange rate has a positive effect on Net Asset Value. And BI 7 Days Repo Rate has a negative effect on Net Asset Value. Meanwhile, based on the short-term test results, the rate of return has a positive effect on Net Asset Value. Inflation has a negative effect on Net Asset Value. Exchange rate has a negative effect on Net Asset Value. And BI 7 Days Repo Rate has a positive effect on Net Asset Value.